Transformasi Digital Akuntansi untuk Meningkatkan Efisiensi Pencatatan Keuangan UMKM Melalui Aplikasi Akuntansiku pada Arsi Dekorasi - Yurike Sindi Gloriana; Mar’atus Solikah; Linawati Linawati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Accurate financial record-keeping is essential for MSMEs, yet many still rely on manual methods. Arsi Dekorasi, for example, had not produced formal financial reports such as income statements or cash flow reports. Digital transformation through accounting applications offers a solution to improve the efficiency and accuracy of financial records. This study aims to explore how the implementation of the Akuntansiku application enhances financial recording efficiency at Arsi Dekorasi. Using a qualitative approach with a case study method, data were collected through in-depth interviews, participant observation, and documentation, and analyzed using the Diffusion of Innovation framework. The findings reveal that prior to using the application, records were manually kept and incomplete. After adopting Akuntansiku, financial recording became more efficient, accurate, and capable of generating automatic reports. Initial technology-related challenges were resolved through mentoring. The digital transformation proved to positively impact both the efficiency and quality of financial records. The study highlights the crucial role of management in sustaining and developing financial digitalization through continuous training and capacity building.